Static Anthropometric Characteristics of Bangladeshi Vehicle Driver: A Case Study. (7th August 2016) - Halder, P. K.; Sarker, E.
Abstract : Background . Inappropriate design of sitting furniture and working equipment causes the serious musculoskeletal injuries and various pains as well as reducing working efficiency. Uncomfortable sitting posture in prolonged driving in Bangladesh is an issue to be solved immediately. Therefore, anthropometric databank of user population is significantly essential for the suitable dimensional design for avoiding these remarkable problems. Methods . This study analyses the anthropometric data of the Bangladeshi male vehicle driver aged between 30 and 60 years. A total of 210 Bangladeshi healthy drivers are considered for 15 anthropometric measurements and compared with the similar anthropometrics of other nationalities. Results. The mean stature and sitting height erect of Bangladeshi driver are 1645 mm and 843 mm, respectively. The mean of body mass index (BMI) of the drivers is 26.09 kg/m 2, which indicates that the drivers are overweight. The mean stature of Bangladeshi driver is 17 mm shorter than the driver of Korea and 115 mm shorter than the driver of Iran. Conclusion . There are substantial differences between the body dimensions of Bangladeshi driver and similar dimensions of other countries. In comparison, Bangladeshi driver is found to be the shortest compared with the sample of other nationalities.